2017
DOI: 10.1155/2017/2176460
|View full text |Cite
|
Sign up to set email alerts
|

Eg5 Overexpression Is Predictive of Poor Prognosis in Hepatocellular Carcinoma Patients

Abstract: Eg5 (kinesin spindle protein) plays an essential role in mitosis. Inhibition of Eg5 function results in cell cycle arrest at mitosis, which leads to cell death. To date, Eg5 expression and its prognostic significance have not been studied in hepatocellular carcinoma (HCC). In this study, 26 freshly frozen HCC tissue samples and matched peritumoral tissue samples were evaluated with a one-step qPCR test and immunohistochemical (IHC) analysis was conducted on 156 HCC samples to investigate the relationships amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 35 publications
4
21
0
Order By: Relevance
“…Therefore, the ndings of the present study provide a rationale for the clinical development of speci c Eg5 inhibitors for HCC treatment. Our ndings regarding the prognostic value of Eg5 expression are generally consistent with those of a previous study [24], although that study did not analyze DFS and used immunohistochemical staining, rather than quanti ed RNA expression, to evaluate tumor Eg5 expression levels.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the ndings of the present study provide a rationale for the clinical development of speci c Eg5 inhibitors for HCC treatment. Our ndings regarding the prognostic value of Eg5 expression are generally consistent with those of a previous study [24], although that study did not analyze DFS and used immunohistochemical staining, rather than quanti ed RNA expression, to evaluate tumor Eg5 expression levels.…”
Section: Discussionsupporting
confidence: 88%
“…However, KIF-speci c inhibitors allegedly prevent the growth and self-renewal of glioblastoma tumor stem cells [49]. Additionally, KIF11 is highly expressed in HCC and is associated with liver cirrhosis and TNM staging and can be used as a poor prognostic biomarker [50]. We demonstrate here that the high expression of KIF11 in HCC tissues is linked to negative OS, negative RFS, and negative PFS.…”
Section: Discussionmentioning
confidence: 70%
“…Then, quantitative PCR was performed using the SYBR MasterMix (4913850001, Roche, Basel, Switzerland), ABI 7900HT, according to the manufacturer's instructions, and then the difference was calculated using the 2 – ΔΔ CT . KIF11 primer is as follows: forward 5′-GAA CAATCATTAGCAGCAGAA-3′ and reverse 5′-TCAGTATAGACA CCACAGTTG-3′ [ 27 ]. β -Actin primer is as follows: forward primer 5′-TAATCTTCGCCTTAA TACTT-3′ and reverse primer 5′-AGCCTTCATACATCTCAA-3′ [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…KIF11 is broadly expressed in lymph node, bone marrow, and other normal tissues. Recent researches reported that KIF11 was overexpressed in several tumors and associated with the poor prognosis, such as prostate cancer [ 22 ], gastric cancer [ 23 ], non-small cell lung cancer [ 24 ], oral cancer [ 25 ], meningioma [ 26 ], hepatic carcinoma [ 27 ], and pancreatic tumor [ 28 ].…”
Section: Introductionmentioning
confidence: 99%